Evaluation of injury caused by lace bug, Cochlochila bullita (Stål) (Hemiptera: Tingidae) on Cat’s whiskers, Orthosiphon aristatus (Blume) Miq. and Sweet basil, Ocimum basilicum Linnaeus - Tan, Peng Li; Sajap, Ahmad Said; Lee, Seng Hua; Hui, Sin Koh (Springer, 2019)
The Ocimum Tingid, Cochlochila bullita (Stål) (Hemiptera: Tingidae) is an important Hemipteran pest for various economically important plants. This study focused on assessing the feeding injury caused by C. bullita on Cat’s whiskers, Orthosiphon aristatus (Blume) Miq. and Sweet basil, Ocimum basilicum Linnaeus. The injured area and number of faecal spots on the leaves caused by C. bullita were recorded. Leaves chlorophyll content were measured to examine the effect of C. bullita feeding on the leaf chlorophyll content. Result showed that feeding occurred on both sides of the leaves and the damages were clearly apparent on the upper leaf surface. The injured area was more in O. aristatus, 12.89 ± 0.52% compared to O. basilicum, 5.85 ± 0.37%. Chlorophyll reduction in infested O. aristatus was also more, with −6.40 ± 0.17 μg / cm2 compared to O. basilicum with only −3.13 ± 0.11 μg / cm2 after 3 days of infestation. Oviposition of C. bullita into midribs were observed and it nearly blocked the vascular tissues. However, these insertions seemed not to harm the plant in short-term, but damage occurs when the nymphs hatch and feed the plants. Overall, O. aristatus seems to be less tolerant to C. bullita infestation as compared to O. basilicum. Beyond the aesthetic damage caused by C. bullita on O. arisatus, severe reduction of chlorophyll due to feeding-induced stress complicated the physiological process of the plant.